2014
DOI: 10.1590/0004-282x20140070
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy has no higher costs than ventriculoperitoneal shunt

Abstract: Objective: To evaluate the cost of endoscopic third ventriculostomy (ETV) compared to ventriculoperitoneal shunt (VPS) in the treatment of hydrocephalus in children. Method: We studied 103 children with hydrocephalus, 52 of which were treated with ETV and 51 with VPS in a prospective cohort. Treatment costs were compared within the first year after surgery, including subsequent surgery or hospitalization. Results: Twenty (38.4%) of the 52 children treated with VPS needed another procedure due to shunt failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This finding is consistent with other studies in the published literature. [ 3 , 10 , 15 , 20 ] This is likely due to the nature of the procedure itself. While VPS involves the use of a foreign body, which is prone to infection and blockage, ETV does not.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies in the published literature. [ 3 , 10 , 15 , 20 ] This is likely due to the nature of the procedure itself. While VPS involves the use of a foreign body, which is prone to infection and blockage, ETV does not.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors reported in the previous studies may affect surgery result as surgeon skills, cost of surgery and surgery instruments. Lima et al 2014 concluded that ETV is not higher than VP shunt but nearly the same as another operation is needed in children due to shunt failure [18]. The largest study of ETV success in very young children was conducted in Uganda and involved 153 children younger than one year.…”
Section: Discussionmentioning
confidence: 99%
“…Second, neither the Brazilian nor the Canadian study found cost differences between ETV and VPS. 6,10 It is worth noting that the overall cost infrastructure, insurance structure, and patient payment systems of Brazil and Canada greatly differ from those of the United States. The results of cost-effectiveness analyses and the success and failure rates used in our study are etiology-and intervention-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators in Canada and Brazil (in 2001 and 2014, respectively) conducted cost analyses for ETV, and both studies found no differences in costs when comparing ETV procedures to other CSF diversion procedures. 6,10 Since the patient population and healthcare infrastructure of the United States is different from that of other countries, such as Brazil and Canada, further investigation is warranted. A systematic evaluation of hydrocephalus etiology and long-term financial impact of hydrocephalus treatment is critically important due to the overall rise in healthcare expenditures in the United States and is therefore the aim of this study.…”
mentioning
confidence: 99%